Pemberdayaan Masyarakat dalam Pencegahahan Stunting di Desa Sarirejo Kecamatan Balen Kabupaten Bojonegoro - M. Arju Ilmi Atho'illah; Siti Rahayu Nadhiroh (Media Gizi Kesmas, 2023)
Background: Bojonegoro Regency is one of the main concerns in the stunting reduction program in East Java. Based on Bojonegoro Regency health profile data, stunting cases in Bojonegoro Regency in 2021 reached 4,227 cases or 5.71%. Risk factors for stunting include environmental factors, parenting patterns, knowledge, family income, behavior, and other factors. Objective: This study aims to provide solutions to operational problems in the implementation of stunting prevention programs in Sarirejo Village. Methods: This research was conducted at the Field Work Practice of the Faculty of Public Health, Universitas Airlangga for the period July – August 2021 for 5 weeks, referring to the PRECEDE-PROCEED framework which can help planning a health program to analyze health situations and programs effectively and efficiently. The research sample was 49 mothers who had babies and toddlers. Data collection techniques using concurrent mixed methods. Results: There were 3 (three) activities carried out in the stunting prevention empowerment program. The intervention program focuses on increasing knowledge in providing food menus for infants and toddlers, providing information related to stunting knowledge. a cooking competition that aims to develop mother's creativity in making healthy food menus for complementary feeding and toddler food by relying on the types of vegetables, side dishes and food sources available in the village itself and in accordance with the people's purchasing power. In addition, stunting counseling activities were also held which aimed to increase mother's knowledge regarding stunting, then made a booklet containing various complementary feeding menus as well as illustrative explanations about stunting knowledge. Conclusion: The health empowerment program in Sarirejo Village is aimed at addressing priority health problems for stunting infants and toddlers. All empowerment programs have achieved success indicators and were able to increase maternal enthusiasm and knowledge in the stunting prevention process in Sarirejo Village.